2019
DOI: 10.1109/tvcg.2018.2859974
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Command Line Workflow for a Package Management System Using ASCII DAG Visualization

Abstract: Package managers provide ease of access to applications by removing the time-consuming and sometimes completely prohibitive barrier of successfully building, installing, and maintaining the software for a system. A package dependency contains dependencies between all packages required to build and run the target software. Package management system developers, package maintainers, and users may consult the dependency graph when a simple listing is insufficient for their analyses. However, users working in a rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…To reduce visual complexity and improve readability, graph data is often visualized as trees [3,29], including the case of CCTs and call graphs [1,7,42,43]. Here, we discuss related work in the area of call graphs, tree ensembles, and graphs in general.…”
Section: Related Workmentioning
confidence: 99%
“…To reduce visual complexity and improve readability, graph data is often visualized as trees [3,29], including the case of CCTs and call graphs [1,7,42,43]. Here, we discuss related work in the area of call graphs, tree ensembles, and graphs in general.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers have investigated the modeling and visualization of dependency graphs [21,17,18,22,30,31,15,23,14,20]. For example, Falke et al suggested a hierarchical graph layout for visualizing the functional dependency graph of software applications; by using a hierarchical layout, users can view the top-level nodes as a first overview and step-wise unfold the nodes on demand to look into details [15].…”
Section: Related Workmentioning
confidence: 99%
“…As Bergle et al [8] suggested, adequately visualizing software dependencies as graph is a non-trivial problem due to the multi-dimensional nature of software, the technique of dependency visualization varies from different aspect to aspect of the software. Isaacs et al [20] developed an interactive dependency graph visualization that utilizes ASCII and brings a full dependency graph through the command line with certain degree of interactions, Fig. 2.5 shown as example on dia 6 specified in Spack management tool.…”
Section: Related Workmentioning
confidence: 99%
“…VR City enables users to observe and interact with a visual representation of source code that is displayed in a virtual reality environment. Another study (Isaacs and Gamblin, 2018) employs a directed acyclic graph to analyze dependencies of package management systems. Ravel (Isaacs et al, 2014) allows users to visualize the behaviour of a software system during the execution of a program based on log traces.…”
Section: Classification By Software System Aspectsmentioning
confidence: 99%